Impact of glucose and lipid metabolic disorders on the risk of chronic post-operative pain syndrome after colorectal cancer surgery - Li, Shuaichao; Fan, Longxin; Meng, Tao; Gao, Zhengjie (Frontiers in Oncology, 2025)
BackgroundThe influencing factors of post-operative chronic pain syndrome after colorectal cancer surgery (POCPS-CCCS) remain unclear. This study aimed to explore the impact of glucose and lipid metabolic disorders on the risk of this postoperative complication.MethodsCase-control study: At 3 months after surgery (defined as baseline), 513 colorectal cancer patients were divided into chronic pain group and control group based on their POCPS-CCCS status. Multivariate logistic or linear regression was used to analyze the associations of glucose and lipid metabolic disorders and peripheral inflammation (assessed via IL-1β, IL-6, and TNF-α) with the risk of POCPS-CCCS. Cohort study: Among the 513 patients, 352 without POCPS-CCCS at baseline were further divided into metabolic disorder subgroup and metabolic normal subgroup according to their baseline glucose and lipid metabolic status. Over a 9-month follow-up (from 4 to 12 months after surgery), multivariate logistic or linear regression was used to investigate the impacts of the metabolic disorders and peripheral inflammation at baseline on the risk of POCPS-CCCS during the follow-up. In both study components, the associations of the metabolic disorders, peripheral inflammation, and POCPS-CCCS with patients’ depression, anxiety, and quality of life scores were also evaluated.ResultsCombined findings from the case-control and cohort studies showed that: At baseline, glucose and lipid metabolic disorders were significantly associated with elevated peripheral inflammation (all P<0.05). The metabolic disorders and elevated peripheral inflammation at baseline were associated with an increased risk of POCPS-CCCS during the follow-up (all P<0.05). Furthermore, the baseline metabolic disorders, elevated baseline peripheral inflammation, and incident POCPS-CCCS during the follow-up were associated with worse depression, anxiety, and lower quality of life scores at the follow-up end (all P<0.05).ConclusionThese results preliminarily indicate that glucose and lipid metabolic disorders, together with peripheral inflammation, may promote the development of POCPS-CCCS. Additionally, these metabolic and inflammatory disorders, alongside POCPS-CCCS, may further impair patients’ psychological status and quality of life. Thus, improving these pathophysiological abnormalities and reducing the risk of this postoperative complication may contribute to health maintenance in patients after colorectal cancer surgery.